2014
DOI: 10.1016/j.ijsu.2014.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of obesity and diabetes mellitus to other primary cancers in surgically treated gastric cancer patients

Abstract: There is a need to be aware of the possibility of OPC in GC patients with DM/obesity. They should undergo intensive screening for OPC before and after gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…Green et al [ 13 ] reported that an OPM was observed in approximately 8% of advanced GC patients and 32% of early GC patients. Our previous study also showed that OPM was observed in 25% of GC patients [ 14 ]. In the present study, the incidence of OPM was 21.5%.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Green et al [ 13 ] reported that an OPM was observed in approximately 8% of advanced GC patients and 32% of early GC patients. Our previous study also showed that OPM was observed in 25% of GC patients [ 14 ]. In the present study, the incidence of OPM was 21.5%.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, the presence of a preoperative OPM was an independent prognostic factor for OS. Our previous study also showed that GC patients with synchronous OPMs had a worse outcome after surgery than those without it [ 14 ]. Furthermore, Kim et al [ 6 ] regarded that the presence of synchronous and metachronous OPMs negatively affected the clinical outcome of GC survivors.…”
Section: Discussionmentioning
confidence: 97%
“…The rarest combination was that of CRC and skin cancer, which was found in only 1 of 117 patients with MPMs (3). For patients with gastric cancer, Takeuchi et al (13) reported that MPMs were observed in 109 patients (25.1%): 40 (9.2%) with synchronous and 76 (18.2%) with metachronous MPMs. The most common malignancy was colorectal cancer (22.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Periodic cancer screening and radical resection with regional lymph node dissection have significantly improved the clinical outcomes of patients with GC [3,5]. However, the synchronous presence of another primary malignancy negatively affected the clinical outcomes of GC survivors [5,6]. Kim et al have hypothesized that synchronous cancers prevented the proper treatment of GC5.…”
Section: Discussionmentioning
confidence: 99%